Explaining Auschwitz and Hiroshima : Historians and the Second World War, 1945-1990. - Bosworth, R. J. B. (New international history series., 1993)
Explores the way in which the main combatant societies of the Second World War have historicised that experience. Bosworth argues that the traumatic history of the war has remained crucial to the politics of post-war societies.